Analisis Komparatif Produksi dan Pendapatan Petani Kakao yang Melakukan Sambung Samping dan yang Tidak Melakukan Sambung Samping Desa Andomesinggo di Kecamatan Besulutu Kabupaten Konawe - Lumampa, Jein Stella; Saediman, Saediman; Limi, Muhammad Aswar (Department of Agribusiness, Halu Oleo University, 2019)
This study aims to determine (1) the production and income of cocoa farmers who do side grafting and cocoa farmers who do not do side grafting, (2) to determine the differences in production and income of cocoa farmers who do side grafting and who do not do side grafting. The population in this study were 150 cocoa farmers, using the proportionate stratified random sampling method obtained by 35 cocoa farmers who conducted side grafting and 25 cocoa farmers who did not do side grafting as the study sample. The results showed that (1) the average production of respondents of cocoa farmers who did side grafting was 316 kg / ha and cocoa farmers who did not do side grafting were 238 kg / ha, production in side grafting farmers and farmers who did not sidegrafting was significantly different with t_count = 0,024 greater than significance Î± = 0,05 (0,024<0,05) with a confidence level of 95% (2) the average income of respondents of cocoa farmers who did side grafting amounting to IDR 4.118.378 and cocoa farmers who did not sidegraftingfrom to IDR. 2.625.712 income for side-grafting farmers and non-side-grading is significantly different with t-count = 0.006 greater than significance Î± = 0.05 (0.006<0.05) with a confidence level of 95%.